Influence of Service Quality and Perceived Value on Repurchase Intention through Customer Satisfaction at CV. Andalan Kita Jepara - Sisno Riyoko; Anna Widiastuti; Sahmu Thariq Hikam (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Fierce competition in the printing and advertising services industry requires companies to be able to retain customers by improving service quality and customer perceived value. This study aims to analyze the effect of service quality and perceived value on repurchase intention with customer satisfaction as a mediating variable at CV. Andalan Kita Jepara. This study uses a quantitative approach with a survey method of 140 customers who have used the services of CV. Andalan Kita Jepara and Jepara residents, with a purposive sampling technique. Data were analyzed using the Partial Least Square (PLS) method through the SmartPLS application version 4.0. The results show that perceived value has a positive and significant effect on customer satisfaction and repurchase intention. Customer satisfaction also has a positive and significant effect on repurchase intention. Meanwhile, service quality does not have a significant effect on customer satisfaction, but has a positive and significant direct effect on repurchase intention. In addition, customer satisfaction is proven to mediate the effect of perceived value on repurchase intention, but does not mediate the effect of service quality on repurchase intention. This research provides an empirical contribution to the development of service marketing studies, particularly in the printing and advertising sectors, by emphasizing the importance of customer perceived value and customer satisfaction in driving repeat purchase intentions.